Synthesis and SAR studies of pyrazole-3-carboxamides and-3-carbonyl thioureides including chiral moiety: Novel candidates as antibacterial agents - Bildirici, Ishak; Cetin, Adnan; Menges, Nurettin; Alan, Yusuf (SERBIAN CHEMICAL SOC, 2018)
A series of tetrasubstituted pyrazole-3-carboxamides (3a-c) and pyrazole-3-carbonyl thioureides (6a-c) were synthesized and their structures characterized by IR, NMR and elemental analysis. The antibacterial potential against specific Gram-positive and Gram-negative strains and the antifungal activities of all novel compounds were investigated. Structure-activity relationships (SAR) studies and some theoretical parameters (ClogP, CMR, PSA and ESP) of the compounds were performed on these two pyrazole derivatives. Pyrazole-3-carboxylate ester 2 was used for the synthesis of the carboxamide derivatives. The reactions of pyrazole-3-carbonyl isothiocyanate 5 with appropriate chiral amino alcohols were utilized for synthesizing the thioureide derivatives. Both of these types of pyrazole derivatives including a chiral moiety exhibited pronounced antibacterial activities. According to the present in vitro study, some of the promising compounds might be new candidates for a new generation of antibacterial drugs.
Keywords: biological activity; chiral amino alcohols; pyrazole; heterocyclic compounds